EVALUSI PENGETAHUAN IBU DAN PEMBENTUKAN KADER BUDARMI DALAM UPAYA PENCEGAHAN ANEMIA PADA ANAK - Chynthia Pradiftha Sari; Siti Zahliyatul Munawiroh; Suci Hanifah; Ika Fidianigsih (P3M Universitas Aisyiyah Surakarta, 2023)
Anemia is a condition in which the hemoglobin (Hb) value in the blood is less than normal. Anemia conditions occur in many children, affecting the development of organs, decreased concentration and learning achievement of children, and endurance. This service program aims to increase knowledge and form cadres of anemia aware mothers (BUDARMI) in the RA Afkaaruna school environment. The community service method uses the Quasy experimental non-control group design method by filling out a pre-test and post-test knowledge questionnaire. The program targets are parents (n=20), given education/counseling on Anemia topics including; definition, etiology, risk factors, prevention, and healthy food ingredients to prevent anemia. After receiving education, the BUDARMI cadres, who are the parents of students, are trained to select and create healthy eating menus to prevent anemia for children. The level of knowledge of program targets was analyzed descriptively and presented as a percentage. This service program showed that 60% of mothers had a good experience with anemia, and 40% were moderate; BUDARMI cadres have been formed within RA Afkaaruna who can select and create healthy menus to prevent anemia in children.Â